Persistent Mullerian Duct Syndrome with Transverse Testicular Ectopia - Kumar, P. Naresh (J Surg Tech Case Rep, 2015)
Persistent Mullerian duct syndrome (PMDS) is a rare form of male pseudohermaphroditism characterized by the presence of Mullerian duct structures in a normal male with 46, XY karyotype. Transverse testicular ectopia (TTE) is rare form of testicular ectopia in which two testes are located on one inguinal side. The opposite scrotum is empty. PMDS with TTE is rare. We report a case of PMDS with TTE discovered during surgery for a right inguinal hernia in a 25-year-old male.